A comparison of sociobehavioral impact on cognitive preservation in Alzheimer's disease between Taiwan and Korea: A cross-national study. Issue 15 (April 2020) - Hsieh, Sun-Wung; Kim, Sang-Yun; Shim, Yong-Soo; Huang, Ling-Chun; Yang, Yuan-Han
Abstract : Abstract: Both Taiwan and Korea are developed countries with different cultures. When encountering the issue of dementia, such sociobehavioral factors have various and different impacts on dementia. We aim to assess the cross-national difference of sociobehavioral impact on cognitive preservation in Alzheimer's disease (AD) between Taiwan and Korea. A uniformed data set was administered regarding AD. We evaluated annual cognitive function using the Mini-Mental State Examination (MMSE), Clinical Dementia Rating sum of box (CDR-SB), and CDR for 2 continuous years. Annual change of scores compared with the baseline indicated cognitive change as preservation or decline. We recorded the sociodemographic variables of interest, including education duration, level of independence, living situation, and marital status. Step-wise regression analyses were performed to determine the independent factors for cognitive preservation. In total, 503 participants in Taiwan and 77 participants in Korea were recruited from 2011 to 2014. The baseline demographic characteristics were different in levels of education, living situation, level of independence, and dementia severity between the 2 countries. With follow-up for 2 years, cognitive preservation was associated with CDR staging at baseline and independence [adjusted odds ratio (OR) = 1.657, 95% confidence interval (95% CI) = 1.109–2.477, P  = .014] in the Taiwanese population, whereas cognitive preservation was related to living alone (adjusted OR = 3.316, 95% CI = 1.135–9.687, P  = .028) in the Korean population. The levels of education showed inconsistency in cognitive preservation in both countries. Cognitive preservation was associated with independence in the Taiwanese population, whereas cognitive preservation was related to living alone in the Korean population. By practicing relevant socioeconomic support, this might contribute to lessening the negative impact of dementia and preserving cognition in different countries. Abstract : Supplemental Digital Content is available in the text